Review of International Registers of Patients with Systemic Juvenile Idiopathic Arthritis - Ekaterina I. Alekseeva; Olga L. Lomakina; Saniya I. Valieva; Tatiana M. Bzarova (Вопросы современной педиатрии, 2017)
The article describes the international experience in monitoring of patients with juvenile idiopathic arthritis. The main goal of most existing international registers of children with juvenile idiopathic arthritis is to evaluate various aspects of the effectiveness and safetyof genetic engineering biological drugs in comparison with methotrexate. No results from the analysis of the effectiveness of registers as a tool for long-term monitoring of the disease and medical care for children with systemic juvenile idiopathic arthritis have beenfound in the available literature.